Seasonal evolution of supraglacial lakes on a floating ice tongue, Petermann Glacier, Greenland - Grant J. Macdonald; Alison F. Banwell; Douglas R. MacAyeal (Annals of Glaciology, 2018)
Supraglacial lakes are known to trigger Antarctic ice-shelf instability and break-up. However, to date, no study has focused on lakes on Greenland's floating termini. Here, we apply lake boundary/area and depth algorithms to Landsat 8 imagery to analyse the inter- and intraseasonal evolution of supraglacial lakes across Petermann Glacier's (81°N) floating tongue from 2014 to 2016, while also comparing these lakes to those on the grounded ice. Lakes start to fill in June and quickly peak in total number, volume and area in late June/early July in response to increases in air temperatures. However, through July and August, total lake number, volume and area all decline, despite sustained high temperatures. These observations may be explained by the transportation of meltwater into the ocean by a river, and by lake drainage events on the floating tongue. Further, as mean lake depth remains relatively constant during this time, we suggest that a large proportion of the lakes that drain, do so completely, likely by rapid hydrofracture. The mean areas of lakes on the tongue are only ~20% of those on the grounded ice and exhibit lower variability in maximum and mean depth, differences likely attributable to the contrasting formation processes of lakes in each environment.